Overall Equipment Effectiveness Analysis Using Discrete Event Simulation at Table Tennis Table Manufacturer - Yuniaristanto; Iqbal Wahyu Saputra; Muhammad Hisjam (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2020)
To measure the performance of the production process, an efficiency calculation is performed using the Overall Equipment Effectiveness (OEE) method. OEE can measure various production losses and identify potential developments that can be carried out in a production process. This research is expected to be an input to improve production efficiency. The results of overall equipment effectiveness are then performed using Discrete Event Simulation, which built using STELLA Architect. The result shows that their overall equipment effectiveness scores are below the company goals, and performance rate is their lowest score. These simulation results are expected to be a basis for improvements in the production division, especially at Table Tennis Table Manufacturer.